Tooth and temporary filling material fractures caused by Cavit, Cavit W and Coltosol F: an in vitro study - Bedram Djouiai; Thomas Gerhard Wolf (BMC, 2021)
Abstract Background Tooth fractures can occur after temporary inter-appointment endodontic filling, resulting in not preserving and thus extraction of the affected tooth. The purpose of this investigation was therefore to evaluate the tooth substance fracture potential given by the expansion of endodontic temporary filling materials. Methods Tooth and access cavities were prepared in 80 mandibular molars. Four groups of 20 teeth each (Cavit, Cavit W and Coltosol F and control) were included. To simulate a clinical situation, the teeth were endodontically pre-treated and a calcium hydroxide dressing was placed. The cavities were filled with the corresponding temporary filling material, with exception of the control group, and kept submerged in distilled water for 15 days. The teeth were examined every 24 h by two calibrated observers under a stereomicroscope (7.5×), fractures of the temporary filling material and tooth structure were photo-documented, and the results statistically analyzed. Kaplan-Meier survival analysis were calculated to illustrate (survival = no fracture) probabilities to evaluate the time when the temporary filling material, tooth structure or both together occurred. Log-rank test was performed in order to assess significant differences between the materials and the subgroups used. Results Fractures were observed only in the Coltosol F group (p < 0.01), at the end of the observation period, a total of 13 teeth (65%) showed temporary filling material and eight teeth (40%) showed tooth structure fractures. No fractures in the pulp chamber area were observed at the end of the observation period in any group. Conclusions Within the limitations of the current in vitro study, the results obtained suggest that tooth structure fractures caused by a temporary filling material can occur during endodontic treatment, thus compromising the success of the treatment.